The effects of whole-body vibration with plyometric training on physical performance in basketball players - Günsel Usgu; İnci Yüksel (My University, 2022)
Objective: The aim of this study is to determine the effects of whole-body vibration (WBV) with plyometric training on physical performance parameters and balance in basketball players. Materials and Methods: Professional basketball players (n=24, age 23.2±6.1 years) were randomly allocated to plyometric training (PT) and plyometric training with WBV (PT+WBV) groups (n=12 each). PT and PT+WBV groups received the same plyometric training program on a whole-body vibration platform for six weeks (two days a week) with routine basketball training. WBV was turned off for the PT group. Jumping performance, strength, speed, agility, flexibility and balance were assessed for all participants. We measured jumping performance using the vertical jump height, strength using the one-repetition maximum (1-RM) half-squat strength test, speed using the 20-meter speed test, agility using the T agility test, flexibility using the sit and reach test, balance using star excursion balance test (SEBT) before and after six weeks of plyometric training in both groups. Results: At the end of six weeks of plyometric training, both groups revealed a significant increase in performance parameters and balance (p<0.05) comparing with pre-training. However, improvements in jumping performance, strength, speed and agility parameters, and balance were statistically greater in the group receiving whole body vibration compared with the plyometric training group (p<0.05). Conclusion: Adding whole body vibration to plyometric training especially in professional athlete's workout programs can result in improvement in physical performance parameters including jumping performance, strength, speed, agility, flexibility, and balance.
Keywords: physical fitness; Plyometric exercise; whole-body vibration